2008
DOI: 10.1111/j.1461-9563.2008.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Ant predation on red oak borer confirmed by field observation and molecular gut‐content analysis

Abstract: 1 Populations of an indigenous longhorn beetle, the red oak borer Enaphalodes rufulus (Haldeman) (Coleoptera: Cerambycidae), recently reached epidemic levels in the Ozark National Forests of Arkansas and Missouri, resulting in extensive tree mortality. 2 The factors regulating E. rufulus populations are largely unknown. Ants appear to be the most abundant potential predators in the Ozarks and have been shown to play a role in regulating populations of other forest insects. 3 The main objective of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Experimental studies on natural enemies of E. rufulus suggest they likely have the most impact during the very earliest life stages (egg or newly eclosed larvae) that we were not able to include in our life tables. Muilenburg et al (2008) found that after artiÞcial placement of E. rufulus eggs on bark, 72% of them were carried off within 1 h or by ants (mostly C. pennsylvanicus and A. tennesseensis); E. rufulus DNA was then later found in Þeld-collected ant guts despite evidence of extremely low E. rufulus egg density during that year. Although we found ants in a small percentage of empty E. rufulus galleries within some trees, it was unclear whether ants were actually predators of E. rufulus or whether they were simply using empty gallery space as cover.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Experimental studies on natural enemies of E. rufulus suggest they likely have the most impact during the very earliest life stages (egg or newly eclosed larvae) that we were not able to include in our life tables. Muilenburg et al (2008) found that after artiÞcial placement of E. rufulus eggs on bark, 72% of them were carried off within 1 h or by ants (mostly C. pennsylvanicus and A. tennesseensis); E. rufulus DNA was then later found in Þeld-collected ant guts despite evidence of extremely low E. rufulus egg density during that year. Although we found ants in a small percentage of empty E. rufulus galleries within some trees, it was unclear whether ants were actually predators of E. rufulus or whether they were simply using empty gallery space as cover.…”
Section: Discussionmentioning
confidence: 97%
“…Emergence of these cryptic beetles occurs at night; they remain nocturnal and do not feed for their approximate 3-wk adult lifespan (Hay 1972a, Solomon 1995. Females oviposit Ϸ120 eggs singly or in groups of 2Ð 4 in difÞcult to detect positions under lichens or in bark crevices (Hay 1969, Donley 1978, Fierke et al 2005a, Muilenburg et al 2008. Eggs hatch into larvae within 10 Ð13 d, chew directly through the bark into the phloem and create Ϸ4 cm 2 oval-, teardrop-, or circular-shaped phloem galleries from July or August through November where they spend their Þrst winter in quiescence (Hay 1969, Fierke et al 2005a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from multiple studies confirms that carpenter ants are predators of a variety of forest pests (Parmelee 1941;Allen et al 1970;Smirnoff 1959;Youngs and Campbell 1984;Feicht and Acciavatti 1985;Galford 1985). Muilenberg et al (2008) reported that 2 species of ants, black carpenter ants, Camponotus pennsylvanicus DeGeer (Hymenoptera: Formicidae), and Aphaenogaster tennessensis Mayr removed 70% of artificially planted red oak borer eggs from tree surfaces in 1 h. Red oak borer DNA was detected in the guts of field-collected black carpenter ants, further confirming their role as predators of red oak borer (Muilenberg et al 2008). Red oak borers laid an average of 119 eggs per female, with a mean egg viability of 99% (Donley 1978), suggesting that without significant egg predation, rates of tree colonization may be very high.…”
Section: Introductionmentioning
confidence: 58%
“…We speculate that at least three factors (predators, host volatiles, and outer bark defenses) may be important in inßuencing host susceptibility at time of initial colonization. Predation in the forest of E. rufulus eggs by carpenter ants [Camponotus pennsylvanicus (De Geer)] was established by Muilenburg et al (2008), although we are unsure of any changes in carpenter ant populations between the two cohorts. Less infested hosts may contain greater numbers of egg and Þrst-instar larval predators (Galford 1986, Verble and).…”
Section: Discussionmentioning
confidence: 99%